Prostanoid EP(1) receptor as the target of (−)-epigallocatechin-3-gallate in suppressing hepatocellular carcinoma cells in vitro - Jin, Juan (Nature Publishing Group, 2012)
AIM: To investigate the effects of (−)-epigallocatechin-3-gallate (EGCG), an active compound in green tea, on prostaglandin E(2) (PGE(2))-induced proliferation and migration, and the expression of prostanoid EP(1) receptors in hepatocellular carcinoma (HCC) cells. METHODS: HCC cell line HepG2, human hepatoma cell lines MHCC-97L, MHCC-97H and human hepatocyte cell line L02 were used. Cell viability was analyzed using MTT assay. PGE(2) production was determined with immunoassay. Wound healing assay and transwell filter assay were employed to assess the extent of HCC cell migration. The expression of EP(1) receptor and Gq protein were examined using Western blot assay. RESULTS: PGE(2) (4-40000 nmol/L) or the EP(1) receptor agonist ONO-DI-004 (400-4000 nmol/L) increased the viability and migration of HepG2 cells in concentration-dependent manners. EGCG (100 μg/mL) significantly inhibited the viability and migration of HepG2 cells induced by PGE(2) or ONO-DI-004. HepG2 cells secreted an abundant amount of PGE(2) into the medium, and EGCG (100 μg/mL) significantly inhibited the PGE(2)production and EP(1) receptor expression in HepG2 cells. EGCG (100 μg/mL) also inhibited the viability of MHCC-97L cells, but not that of MHCC-97H cells. Both EGCG (100 μg/mL) and EP(1) receptor antagonist ONO-8711 inhibited PGE(2) 4 μmol/L and ONO-DI-004 400 nmol/L-induced growth and migration of HepG2 cells. Both EGCG (100 μg/mL) and ONO-8711 210 nmol/L inhibited PGE(2)- and ONO-DI-004-induced EP(1) expression. EGCG and ONO-8711 had synergistic effects in inhibiting EP(1) receptor expression. PGE(2), ONO-DI-004, ONO-8711, and EGCG had no effects on Gq expression in HepG2 cells, respectively. CONCLUSION: These findings suggest that the anti-HCC effects of EGCG might be mediated, at least partially, through the suppressing EP(1) receptor expression and PGE(2) production.